Response of Background Herbivory in Mature Birch Trees to Global Warming - Nakamura, Masahiro; Minoshima, Moeko; Terada, Chisato; Takagi, Kentaro; Makoto, Kobayashi; Shibata, Hideaki; Hiura, Tsutom (Frontiers in Forests and Global Change, 2021)
Given the time scale based on the duration of exposure to global warming, natural climate-gradient studies and experimental manipulations have detected long-term (decades to centuries) and short-term (years to decades) ecological responses to global warming. Combination of these two complementary approaches within a single study may enable prediction of the likely responses of ecological processes to global warming on a realistic time scale. To understand how global warming affects plant–herbivore interactions within a canopy of Erman's birch on a realistic time scale (decades), we combined an elevational gradient study and a warming experiment involving mature birch trees in which the soil and tree branches were warmed separately. In the elevational gradient study, herbivory by chewing insects and plant growth increased as elevation decreased, and the concentrations of condensed tannins and total phenolics in the leaves decreased. In the warming experiment, soil warming alone increased herbivory, and the addition of branch warming amplified the effect on herbivory. Soil warming alone decreased the tannin concentration, and the addition of branch warming led to a further reduction. The variation in herbivory was best explained by the tannin content of leaves. Our experimental results demonstrate that the decreased tannin content of leaves due to a combination of soil and branch warming was an important driver of increased herbivory in the canopy of the mature birch trees. The similar tendencies in the short- and long-term responses imply that global warming is likely to increase background herbivory in mature birch trees on a realistic time scale (decades) by decreasing the tannin content of leaves in the canopy.